Implementation of Pancasila Social Justice Values in Forming Student Civility at State Middle School 7 Batanghari - Sabilla Selomita; Melisa Melisa; Yulistia Opeska (UIN Fatmawati Sukarno Bengkulu, 2026)
This study aims to analyze the implementation of social justice values on civic virtues among students at SMPN 7 Batanghari. The research employs a qualitative approach with a case study design. Data collection techniques include observation, interviews, and documentation with informants consisting of students, Civics Education teachers, and the vice principal for student affairs. Data analysis uses the Miles and Huberman interactive model. The results show that the implementation of social justice values on civic virtues is reflected in three main indicators: (1) attitudes toward justice and equality showing positive tendencies, although there is still a small number of students who feel their group is superior; (2) ethics and civility in interaction that have been implemented through polite and inclusive communication habits; (3) awareness of law and rules at a moderate level with an understanding that rules are made for collective order. The implementation of social justice values is influenced by the role of teachers as role models, school culture, and consistency in rule enforcement